PERSEPSI MAHASISWA TERHADAP PEMBELAJARAN TATAP MUKA PASCA PEMBELAJARAN DARING - Mawadda Warahma Akhmad; Norhidayah Norhidayah; Rosita Ilhami; Nur Aisyah; Danial Danial; Makmur Jaya Nur (LP2M Institut Agama Islam Muhammadiyah Sinjai, 2022)
The impact of the Covid-19 outbreak on the education sector is the learning process that must be carried out online during the outbreak. However, over time, the Covid-19 outbreak began to subside and the learning process began to be carried out face to face. In this study, it discusses student perceptions of face-to-face learning after online learning. The research design used is descriptive qualitative. Data collection techniques using interviews and observation. The results of the study showed that offline learning is more attractive to students because it is easy to implement and offline learning gives them a wider space so that they are more flexible in discussions and ask questions of educators and peers.